2022
DOI: 10.3389/fnagi.2022.919614
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic signatures associated with immune infiltration in Alzheimer’s disease by integrating bioinformatic analysis and machine-learning strategies

Abstract: ObjectiveAs a chronic neurodegenerative disorder, Alzheimer’s disease (AD) is the most common form of progressive dementia. The purpose of this study was to identify diagnostic signatures of AD and the effect of immune cell infiltration in this pathology.MethodsThe expression profiles of GSE109887, GSE122063, GSE28146, and GSE1297 were downloaded from the Gene Expression Omnibus (GEO) database to obtain differentially expressed genes (DEGs) between AD and control brain samples. Functional enrichment analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Using the GEO database, researchers have identified in recent years numerous hub genes that are differentially expressed in AD and control brain samples and have further determined many possible diagnostic biomarkers of AD using the ROC prediction model. Tian et al (2022) identified three hub genes ( MAFF , ADCYAP1 , and ZFP36L1 ; AUC = 0.850) and verified their expression in the AD brain (AUC = 0.935). Wu et al (2021) found 10 hub genes, namely SERPINE1 , ZBTB16 , CD44 , BCL6 , HMOX1 , SLC11A1 , CEACAM8 , ITGA5 , SOCS3 , and IL4R , all of which have good diagnostic value (AUC > 0.75).…”
Section: Discussionmentioning
confidence: 75%
“…Using the GEO database, researchers have identified in recent years numerous hub genes that are differentially expressed in AD and control brain samples and have further determined many possible diagnostic biomarkers of AD using the ROC prediction model. Tian et al (2022) identified three hub genes ( MAFF , ADCYAP1 , and ZFP36L1 ; AUC = 0.850) and verified their expression in the AD brain (AUC = 0.935). Wu et al (2021) found 10 hub genes, namely SERPINE1 , ZBTB16 , CD44 , BCL6 , HMOX1 , SLC11A1 , CEACAM8 , ITGA5 , SOCS3 , and IL4R , all of which have good diagnostic value (AUC > 0.75).…”
Section: Discussionmentioning
confidence: 75%
“…It is reported that PPP1R15A inactivation could increase insulin resistance 31 and play a proinflammatory role through endoplasmic reticulum stress 32 . The decrease of MAFF can inhibit the expression of antioxidant genes and increase the apoptosis of β cells induced by oxidative stress, 33 while the overexpression of MAFF can inhibit the transcription of NF‐E2‐related factors, which leads to immune and inflammatory reactions 34 . GADD45B can be used as a prognostic biomarker in the diagnosis of DN, 35 and it has been proved that the expression of GADD45B is downregulated in synovial tissue of OA 36 .…”
Section: Discussionmentioning
confidence: 99%
“…32 The decrease of MAFF can inhibit the expression of antioxidant genes and increase the apoptosis of β cells induced by oxidative stress, 33 while the overexpression of MAFF can inhibit the transcription of NF-E2-related factors, which leads to immune and inflammatory reactions. 34 GADD45B can be used as a prognostic biomarker in the diagnosis of DN, 35 and it has been proved that the expression of GADD45B is downregulated in synovial tissue of OA. 36 KLF4 can inhibit inflammation and bone destruction in OA, 37 and inhibition of KLF4 expression can promote the conduction of the NF-kB signal pathway and then improve the insulin resistance of macrophages.…”
Section: Bayesian Co-localization Analysismentioning
confidence: 99%
“…Our research comprehensively explored 28 immune cell subsets and various immune-modulators in the AD immune microenvironment, and based on the advantages of machine learning in clinical applications, we finally identified six key immune cell subtypes (plasmacytoid dendritic cell, type 17 T helper cell, immature B cell, natural killer cell, MDSC, and neutrophil) and five vital immune genes (CXCR4, PPP3R1, HSP90AB1, CXCL10, and S100A12) that can accurately predict AD progression, some of which have never been reported in AD before. In addition, recent studies only depict the expression landscape of immune cell subsets or immune-related genes based on small sample sizes, and lack more in-depth studies ( 50 , 70 , 71 ). What’s more, the immune-related molecular subtypes in AD patients also remain unknown and need further clarification.…”
Section: Discussionmentioning
confidence: 99%